Strengthening The Entrepreneurship Spirit and Assistance of Culinary Business Management 'Zizi Bolen' Jember (Indonesian Journal of Devotion and Empowerment, 2022)
The Covid-19 virus and its handling efforts have significantly impacted global and local economic conditions. This condition makes many businesses, especially MSMEs, lose their turnover and are forced to go out of business due to their inability to survive. Some MSMEs are still trying to get back up and try their luck in the business during the pandemic. However, they are constrained by several problems faced by service partners, namely decreased motivation and business management problems, which include inventory management, marketing, and competitive conditions. The method used in community service is the participatory rural appraisal approach. This method allows partners or culinary businesses of “Zizi Bolen” to improve their knowledge and skills with the implementation team as a facilitator. The activities included program socialization, increasing knowledge using lectures, brainstorming and FGDs, and direct assistance. The results are increased partner empowerment in enthusiasm and motivation, product display, and the courage to open promotions through social media. In addition, the Bolen business, which did not have a brand, began to dare to install the “Zizi Bolen” brand and use environmentally friendly cardboard as one of its advantages. Virus Covid-19 dan usaha penanganannya sangat berdampak kepada kondisi ekonomi baik global bahkan sampai kondisi ekonomi lokal. Kondisi tersebut menjadikan banyak usaha khususnya UMKM kehilangan omzet dan terpaksa gulung tikar karena ketidakmampuan dalam bertahan. Namun, masih ada beberapa UMKM yang berusaha untuk bangkit kembali dan mencoba peruntungan bisnis di masa pandemi namun terkendala beberapa masalah yang dihadapi mitra pengabdian yaitu penurunan motivasi, masalah manajemen usaha yang meliputi manajemen persediaan dan pemasaran serta kondisi persaingan. Metode yang dipakai dalam pengabdian kepada masyarakat yang dilakukan adalah pendekatan participatory rural appraisal. Metode ini memungkinkan mitra atau usaha kuliner ““Zizi Bolen”” untuk meningkatkan pengetahuan dan keterampilannya dengan tim pelaksana sebagai fasilitator. Kegiatan yang dilakukan antara lain sosialisasi program, peningkatan pengetahuan dengan cara ceramah, brainstorming dan FGD serta pendampingan langsung. Hasil yang didapat yaitu adanya peningkatan keberdayaan mitra baik dari sisi semangat dan motivasi maupun tampilan produk dan keberanian untuk membuka promosi melalui media sosial. Selain itu, usaha Bolen yang awalnya tidak memiliki merek mulai berani memasang merek ““Zizi Bolen”” dan mulai menggunakan kardus ramah lingkungan sebagai salah satu keunggulannya.